VARIANTS OF MULTICULTURAL DAWAH: WAYS OF RELIGION IN RURAL COMMUNITIES IN THE MODERN ERA - Nikmatur Rosida; Bobby Rachman Santoso (ORASI: Jurnal Dakwah dan Komunikasi, 2023)
In the modern era, da'wah is increasingly required to be carried out according to the social changes existing in society. Not only do Mad'u (da'wah audience) nowadays consume da'wah presented directly by the da'i (preacher), but also through social media and the influence of modernism. Interestingly, in Kesamben Village, some mad'u still listen to the da'wah presented culturally. It indicates that there are variants of da'wah that occur in the lives of rural communities. One of them is multicultural da'wah. Multicultural da'wah is an effort to invite mad'u on the right path amid cultural diversity through tolerance, ukhuwah, and many more. So, there are two main problem formulations, namely (1) What are the da'wah criteria needed by the community in Kesamben Village? and (2) What are the ways in practicing religion amidst cultural diversity? To answer the formulation of the problem, researchers used qualitative research methods with a sociological approach. The primary source used was the Muslim community of Kesamben Village, while the secondary sources were books, journals, and articles related to the research objects. The data collection techniques were observation, interview, and documentation. The research results show that rural communities need da'wah delivered by da'i in a polite, humane, and humorous manner. In addition, village people tend to follow a culture that does not violate Islamic law. Even though the modern era has had a major influence on people's lives, mad'u in Kesamben Village still preserve religious culture by not denying technological developments.